The Model of Sexual Violence Anticipation Among Female Student of 13-17 Years Old based on the Health Belief Model - Triyana Puspa Dewi; Ni Luh Seri Astuti (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2024)
Introduction: Sexual violence is something that is commonly to be experienced by women and teenagers in public or community spaces as the highest victims. It may trigger by several factors that may actually be prevented. This research aims to build a model for anticipating sexual violence among female students aged 13-17 years based on the Health Belief Model.Method: This research is a quantitative study using an explanatory survey design with a cross sectional approach. The respondents included in this study were 110 female students aged 13-17 years from SMPN 13 Denpasar and SMAN 9 Denpasar. The sampling technique used is proportional random sampling and analyzed by the Partial Least Square (PLS), which was a Structural Equation Model (SEM) to test the model.Results: A factor which has a significant influence on the formation of a model for anticipating sexual violence in female students aged 13-17 years based on the health belief model, namely the perception of threat factors (p-value 0,000). This threat perception factor is significantly influenced by modification factors (p-value 0,002) and signaling factors (p-value 0,000). Modification factors in the form of institutional factors are reduced from the model.Conclusions: Factor perception of threats able to mediate influence modification factors and cue factors in actions in the anticipatory model of sexual violence among female students aged 13-17 years based on the health belief model. The benefits of this research can be increased by building a new model that specifically involves female students who have a history of violence.